Energetics of Eddy-Mean Flow Interactions in the Amery Ice Shelf Cavity - Yang Wu; Yang Wu; Zhaomin Wang; Zhaomin Wang; Chengyan Liu; Liangjun Yan (Frontiers in Marine Science, 2021)
Previous studies demonstrated that eddy processes play an important role in ice shelf basal melting and the water mass properties of ice shelf cavities. However, the eddy energy generation and dissipation mechanisms in ice shelf cavities have not been studied systematically. The dynamic processes of the ocean circulation in the Amery Ice Shelf cavity are studied quantitatively through a Lorenz energy cycle approach for the first time by using the outputs of a high-resolution coupled regional ocean-sea ice-ice shelf model. Over the entire sub-ice-shelf cavity, mean available potential energy (MAPE) is the largest energy reservoir (112 TJ), followed by the mean kinetic energy (MKE, 70 TJ) and eddy available potential energy (EAPE, 10 TJ). The eddy kinetic energy (EKE) is the smallest pool (5.5 TJ), which is roughly 8% of the MKE, indicating significantly suppressed eddy activities by the drag stresses at ice shelf base and bottom topography. The total generation rate of available potential energy is about 1.0 GW, almost all of which is generated by basal melting and seawater refreezing, i.e., the so-called “ice pump.” The energy generated by ice pump is mainly dissipated by the ocean-ice shelf and ocean-bottom drag stresses, amounting to 0.3 GW and 0.2 GW, respectively. The EKE is generated through two pathways: the barotropic pathway MAPE→MKE→EKE (0.03 GW) and the baroclinic pathway MAPE→EAPE→EKE (0.2 GW). In addition to directly supplying the EAPE through baroclinic pathway (0.2 GW), MAPE also provides 0.5 GW of power to MKE to facilitate the barotropic pathway.